Respiratory Syncytial Virus Vaccination as Cardiopulmonary and Cardiovascular Risk Mitigation in Adults with Heart Disease - Clara Bonanad; Vivencio Barrios; Guillermo Barreres; Nora Garcia-Collado; Daniela Maidana; David Vivas; Sergio Raposeiras; Elena Fortuny; Diego Segura-Rodriguez; Gonzalo Alonso-Salinas; Esther Redondo; Alberto Garcia-Lledó; et al. (Journal of Clinical Medicine, 2026)
Background/Objectives: Respiratory syncytial virus (RSV) causes morbidity in older adults with cardiovascular disease, in whom infection may precipitate severe lower respiratory tract disease, hospitalization, functional decline, and cardiovascular destabilization. We evaluate the evidence for RSV vaccination in cardiovascular disease and propose a jurisdiction-adaptable framework for integrating vaccination into cardiovascular care. Methods: Observational studies, randomized trials, pragmatic and test-negative studies, prespecified cardiovascular analyses of DAN-RSV, and eligibility recommendations were narratively synthesized and translated into a pathway encompassing patient identification, eligibility and risk assessment, vaccine delivery and co-administration, documentation, and follow-up. Results: Acute cardiac events are frequent during RSV hospitalization, and cardiovascular risk may persist after infection. Randomized trials establish protection against RSV-associated lower respiratory tract disease and respiratory illness, while real-world studies support effectiveness against RSV-related hospitalization. DAN-RSV reduced all-cause cardiorespiratory hospitalization but did not demonstrate significant reductions in cardiovascular hospitalization, myocardial infarction, heart failure (HF) hospitalization, atrial fibrillation, stroke, cardiovascular death, or major adverse cardiovascular events; observational associations with lower post-vaccination cardiovascular-event rates remain hypothesis-generating. The framework prioritizes adults aged ≥75 years and those aged 50–74 years with high-risk cardiovascular conditions where consistent with national recommendations, embeds vaccination assessment across cardiology, HF, primary care, pharmacy, and long-term care, and incorporates co-administration, documentation, and outcome surveillance. Conclusions: The principal contribution is a pathway for moving RSV vaccination from recommendation to routine preventive care for adults with cardiovascular disease. It anchors implementation in established RSV and cardiorespiratory benefits while treating cardiovascular-event reduction as a research priority rather than a demonstrated indication.